Firescapes of disruption: An absence of insurance in landscapes of fire. (June 2021) - Booth, Kate
In this paper, I critically interrogate the expectation that insurance is becoming more present through the processes of financialisation and marketisation – as up-to-date policies and/or in the hearts and minds of consumers. I draw upon interviews about house and contents insurance, with householders in the flammable landscapes of south-eastern Tasmania, Australia. The participants identify these landscapes as resilient and permanent and thus ultimately unaffected by fire. In understanding bush-living as co-constituted with fire and not purely threatened by fire, they experience a strong sense of continuance in these places. In this context, the promise of insurance emerges as contingent, and even if an up-to-date policy is present, insurance moves in and out of focus, is present and becomes absent as various human and non-human actants exert agency. Drawing on critical landscape studies in exploring these spatial contingencies, I observe insuring as landscaping practice. As well as contributing to critical insurance studies and financialisation of everyday life research, I provide a signpost for rethinking the role of insurance in disaster management and climate adaptation.